Detecting radio emission from air showers with LOFAR - Nelles, Anna; Buitink, Stijn; Corstanje, Arthur; Enriquez, Emilio; Falcke, Heino; Frieswijk, Wilfred; Hörandel, Jörg R.; Mevius, Maaijke; Thoudam, Satyendra; Schellart, Pim; Scholten, Olaf; Ter Veen, Sander; et al. (AIP Conference Proceedings, 2013)
LOFAR (the Low Frequency Array) is the largest radio telescope in the world for observing low frequency radio emission from 10 to 240 MHz. In addition to its use as an interferometric array, LOFAR is now routinely used to detect cosmic ray induced air showers by their radio emission. The LOFAR core in the Netherlands has a higher density of antennas than any dedicated cosmic ray experiment in radio. On an area of 12 km2 more than 2300 antennas are installed. They measure the radio emission from air showers with unprecedented precision and, therefore, give the perfect opportunity to disentangle the physical processes which cause the radio emission in air showers. In parallel to ongoing astronomical observations LOFAR is triggered by an array of particle detectors to record time-series containing cosmic-ray pulses. Cosmic rays have been measured with LOFAR since June 2011. We present the results of the first year of data. © 2013 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-08-15
Keywords: cosmic rays; experiments; extensive air showers; interferometry; radio emission; Radio telescope